The Role of Small Historical Towns in Preserving the National Identity (on the Example of Startford-upon-Avon) - Galina I. Povazhnaya (Современная Европа)
The article reveals the potential of small British town culture for preserving the national identity of the British. In the context of globalization processes, there is an erosion of national identity and a clash between the ideology of cosmopolitan elites and traditional values. It is the culture of small towns that allows one to preserve and strengthen national identity. The purpose of the article is to identify the features of the culture of Stratford-upon-Avon as a factor in preserving the ethnonational identity of the British. The author analyses the role of William Shakespeare as a “genius loci” who determines modern cultural practices and mechanisms for the reproduction of traditional British identity, as well as identifies its components that are reproduced in the culture of a small town. Scientific publications, posts from the city’s official website, videos posted on the YouTube portal, as well as the results of the author’s field research were used as research sources. The role of William Shakespeare's work in urban culture is determined. An analysis of the cultural practices of Stratford showed the relevance of such characteristics of British identity as commitment to family values, disposition to charity, awareness of the special value of work, love of the history of their city and country, craving for high art and aristocratic forms of rituals. In addition, it is concluded that according to the European approach culture is an industry capable of gently managing society and a resource of material well-being.